جدلية العلاقة بين الحكم الرشيد والتنمية المستدامة الجزائر نموذجاً - جزان نزار; ساعود ساعود (Latakia University Journal - Economic and Legal Sciences Series, 2016)
ARAB COUNTRIES REPRESENTS A UNIQUE CASE IN TERMS OF OWNERSHIP OF ECONOMIC CAPABILITIES OF A GOOD WHILE LIVING OF ITS CITIZENS TO IMPROVE THE REQUIRED LEVEL NOT SEEN, WHICH SUGGESTS THE EXISTENCE OF A SPECIFIC DEFECT IN THE INVESTMENT OF RESOURCES WHICH MAY BE DUE TO SOME REASONS TO GOVERNANCE STYLE IN TERMS OF THE EFFICIENCY OF THE ADMINISTRATION AND EFFECTIVENESS OF THE METHOD, IN ADDITION TO THE NATURE OF THE STRUCTURAL CONDITIONS REQUIRED FOR SUCH ADMINISTRATION, WHERE HE WAS THE INCLUSION OF THE TECHNICAL DIMENSION OF EFFICIENT ADMINISTRATION AS PART OF THE CONCEPT OF GOOD GOVERNANCE, AS WELL AS OTHER POLITICAL, ECONOMIC AND SOCIAL DIMENSIONS WHICH CONVERGED WITH DIMENSIONS OF SUSTAINABLE DEVELOPMENT IN THE PROCESS OF EVOLVING RELATIONSHIP BETWEEN THE POLITICAL, ECONOMIC AND SOCIAL KAPADIA, AS THE REQUIREMENTS OF SUSTAINABLE DEVELOPMENT SUCCESS IN INVESTMENT OPTIMUM RESOURCES, WHETHER ECONOMIC OR HUMAN IS NOT CORRECT WITHOUT A RATIONAL MANAGEMENT OF THE SAME ELEMENTS AND CHARACTERISTICS OF GOOD GOVERNANCE ENSURES THE EXISTENCE ACHIEVE POLITICAL RESULTS, AS WELL AS ECONOMIC AND SOCIAL OUTCOMES SERVE THE DEVELOPMENT OF COUNTRIES, ESPECIALLY IN THE ARAB COUNTRIES, WHICH HAS THE POTENTIAL TO QUALIFY FOR EXAMPLE, AS A PLACEMENT STUDY. تمثّل البلدان العربية حالة فريدة من حيث امتلاكها لقدرات اقتصادية لا بأس بها, في حين لم يشهد مستوى معيشة مواطنيها التحسن المطلوب، مما يوحي بوجود خلل معين في أسلوب استثمارها لمواردها, الأمر الذي قد يرجع في بعض أسبابه إلى أسلوب إدارة الحكم من حيث كفاءة هذه الإدارة وفعاليتها، إضافة إلى طبيعة الشروط البنيوية التي تتطلبها مثل هذه الإدارة . وقد تم إدراج البعد التقني المتعلق بكفاءة الإدارة بوصفه جزءا من مفهوم الحكم الرشيد ، بالإضافة إلى باقي الأبعاد السياسية والاقتصادية والاجتماعية التي تلاقت مع أبعاد التنمية المستدامة في صدد العلاقة الناشئة بينهما كالبعدين السياسي والاقتصادي والاجتماعي، إذ إن مقتضيات نجاح التنمية المستدامة في استثمار أمثل للموارد سواء الاقتصادية أو البشرية لا يستقيم من دون وجود إدارة عقلانية با لمقومات نفسها وخصائص الحكم الرشيد يضمن وجودها تحقيق نتائج سياسية، علاوة على النتائج الاقتصادية والإجتماعية التي تخدم تطور الدول و لا سيما في البلدان العربية التي تملك مقومات تؤهلها لذلك كموضع الدراسة مثلاً .